Uso da arquitetura PI System para implantação de um sistema de monitoramento de ativos em uma mineradora de bauxita no Baixo Amazonas - SOUSA, Vivian Leite (2022)
The paper describes how an asset condition monitoring system was implemented in a bauxite mining company in the Lower Amazon, based on predictive maintenance techniques, which stands out for its capacity to anticipate failures. To this end, using the PI System tools, data collection and integration of information from various platforms in a single repository, data treatment and analysis of these indicators were carried out and, finally, the visualization screens were developed. The system made it possible to identify the real conditions of the assets and the source of the problem. Thus, contributing to support the predictive maintenance strategy adopted by the company and bringing more confidence to the assets and the process.